A Novel Stretchable Coaxial NiTi‐Sheath/Cu‐Core Composite with High Strength and High Conductivity. (26th November 2012) - Hao, Shijie; Cui, Lishan; Chen, Zonghai; Jiang, Daqiang; Shao, Yang; Jiang, Jiang; Du, Minshu; Wang, Yandong; Brown, Dennis. E.; Ren, Yang
<x xml:space="preserve">Abstract</x> A novel stretchable coaxial NiTi‐sheath/Cu‐core composite wire was fabricated by means of simple mechanical processing. This composite simultaneously possesses high electric conductivity, high strength and superelasticity. This set of properties renders this composite a unique position in the properties chart of all known electrical conductor materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>